Del escenario al palco: Rearticulación del público en Información para extranjeros y Cinema Utoppia - González-Contreras, Melissa (Latin American Theatre Review, 2018)
Theorists and dramatists Bertolt Brecht and Augusto Boal bestow a truth-revealing power to theatre in relation to its social context. In addition, they recognize the fundamental role of the audience as the creator of a play’s meaning and, although to different degrees and manners, push the audience to be an active participant both in theatrical performances as well as the world beyond the theater. This essay analyzes two plays from different settings: Información para extranjeros (1973) by Argentina’s Griselda Gambaro and the Chilean play Cinema Utoppia (1985) by Ramón Griffero. Through these plays I propose that the evolution in the conception of the theatrical character and the innovative use of the stage trigger a subsequent change in the function traditionally attributed to the theatrical audience, reflecting the practices developed by Brecht and Boal. In Gambaro’s and Griffero’s plays, the audience takes on a participatory role during the performance. This transformation of the audience responds to concrete sociopolitical circumstances, revealing certain truths and aiming to stimulate active participation in the sociopolitical processes to which the plays respond.